Analysis of Student Travel Route Determination from Nongsa to Universitas Internasional Batam - Restu Maulana Nashuha; Usmanul Hayadi Umar (Fakultas Teknik Sipil dan Perencanaan, 2023)
Batam is never quiet in traffic activities, especially when traveling to Batam International University. This is characterized by frequent traffic jams on two roads to campus, especially in the morning and evening. Regarding congestion factors that increase travel time, it contributes significantly to the traffic transportation process on the travel route to the campus of Universitas Internasional Batam, especially private vehicles. For this reason, an analysis of the accessibility of private vehicles is needed based on the existing travel routes in Batam to the campus of the International University of Batam. This analytical research is carried out based on time and distance—accessibility parameters based on the percentile statistical method. From the percentile table, the accessibility value is divided into three parts, namely high, medium, and low. The results of the analysis of private vehicles showed six route trips with high accessibility values, five travel routes with medium accessibility values, and seven routes travel with low accessibility values.